Sistem Pendukung Keputusan Penentuan IT Support Perusahan Telekomunikasi Terbaik Menggunakan Metode Moora - Yuyun Dwi Lestari; Muhammad Eka; Rusmin Saragih (UIN Sumatera Utara, 2021)
The success of an organization or company is not a good idea regardless of its resources, one of the resource is human resources that is required to be reliable in completing the work obligations. The process of determining the best employees in an organization or company is a very difficult process and takes a long time to support decisions. There are many methods that can be used in determining the best employees in a company, the Multi-Objective Optimization on The Basis of Ratio Analysis (MOORA) method can be applied to Decision Support Systems because it has a high degree of flexibility and accuracy, in solving the problem of determining the best employees.